Distribution Patterns and Associated Communities of Sea Anemones in the South-Western Mediterranean - Soltani, Lotfi; Bentera , Malika; Bellatreche , Mohammed (Studia Ecologiae et Bioethicae, 2025)
This study investigates the distribution of sea anemone species along the Mediterranean southwest coast (the region of Oran, Mostaganem, Tlemcen/Ain Temouchent) aiming to understand their role as bioindicators and their contribution to biodiversity. Recognizing that anemone distribution is influenced by associated species, this research also examines the co-occurrence of other flora and fauna. A complete census of cnidarians was conducted, and Correspondence Factor Analysis (CFA) was used to analyze the relationships between three species of anemones (Anemonia viridis, Anemonia rustica, and Actinia equina) and their locations. The CFA identified five distinct groups in the spatial distribution of the anemones and associated floral and faunal species. Specifically, one group associated Ulva Lactuca with sites like Saintrock and Marsa El Hadjadj another linked A. rustica to sites like Madagh I and Arzew I; a third group connected Padina pavonica and Cystoseira mediterranea to locations such as Moscarda and Bider; a fourth associated Paracentrotus lividus with La Madrague; and a final group linked A. viridis to sites like Arzew II and Sidi Yochaa. Interestingly, the Shannon index (H) revealed variations in species diversity across the study area. The Tlemcen/Ain Temouchent and Mostaganem area exhibited the highest Shannon index values (some exceeding 1.6), indicating greater diversity, but also included sites with the lowest value (0), suggesting localized impacts on biodiversity. This research provides valuable insights into the distribution patterns of these key cnidarian species and their associated communities, contributing to our understanding of coastal ecosystem biodiversity and is likely to be useful for future conservation efforts in the Mediterranean.